Efektivitas Kepemimpinan Kepala Desa Dalam Menggerakan Partisipasi Masyarakat Dalam Pembangunan Di Desa Kembuan, Kembuan Satu Dan Desa Tonsea Lama Di Kecamatan Tondano Utara - Pangalila, Gredy; Lengkong, Florence Daicy; Tulusan, Femmy (Sam Ratulangi University, 2015)
ABSTRAC: The village government based on law No. 32 of 2004 concerning Regional Governments meant as Community unity village law has limits the jurisdiction, as stipulated in the Constitution of the Republic of Indonesia in 1945. In order to realize the goals of national development, the Government is giving much attention to the development in rural areas. But in fact still encounter some problems and obstacles in the development of the village. This research aims to know the relationship of the effectiveness of the leadership of the village chief with the level of community participation in development in the villages of Kembuan, Kembuan one, and the village of old Town Tonsea in North Tondano. This research uses descriptive method. The data collection has been conducted through kusioner and 80 interviews to informants consisting of: the Government Apparatus Elements 10 men of the village, 10 people's consultative body of the village of Elements (BPD), 10 LPM and elements of the PKK, 10 people elements of Civic social organization, 10 people elements of community leaders, and citizens of 30 people of the general public.The research results showed that respondents perceived leadership Effectiveness is on the category are likely higher and the effectiveness of the leadership of the village chief in the North due to a positive and highly significant effect on community participation in development of the village. The effectiveness of transformational leadership style that implements/democratic tend to be more effective in increasing public participation in the development of the village, especially in the Districts of North Minahasa Regency Tondano. Referring to the results of the findings in this study, then it can put forth suggestions that the head of the village as the formal leader closer to the community, should apply the transformational leadership style with emphasis on democratic/dimensions influence the ideal (example or charismatic) and inspirational motivation so that the dimension is expected to spur an increase in public participation in the development of the village. Key words: effectiveness of the leadership of the village chief in a Drive community participation